Innovations in micropropagation of the orchid Cattleya nobilior: the effect of bioreactor and enriched culture media - Geisianny Pereira Nunes; José Carlos Sorgato; Jéssica Celeste Mônico Ramos; Jackeline Schultz Soares; Rodrigo Kelson Silva Rezende; Rayner Bueno Peinado (Ciência Rural)
ABSTRACT: Cattleya nobilior Rchb.f. is an epiphytic species of ornamental value, facing risks due to environmental threats, indiscriminate collection, and habitat loss. In this context, in vitro cultivation presents a viable alternative for its commercial production and conservation efforts. This pioneering study evaluated the initial in vitro growth and ex vitro establishment of C. nobilior, using supplemented culture media and comparing conventional micropropagation with temporary immersion bioreactors. The experimental design was completely randomized, with treatments in a 4x2 factorial scheme, involving four culture media and two micropropagation systems. After 180 days of in vitro cultivation, the plants were assessed for the number of leaves, pseudobulbs, and roots, length of the largest leaf and root, plant height, pseudobulb diameter, and total fresh mass. Subsequently, they were transplanted into containers with mixed substrate and transferred to an ex vitro environment. After another 180 days, survival was recorded, and the same characteristics initially evaluated were measured again to calculate their increments. The results showed that, in in vitro cultivation, plants grown by the conventional method exhibited tillering, resulting in an increase in the number of leaves, shoots, and roots. However, those cultivated in a bioreactor showed an increase in leaf and root length, pseudobulb diameter, and plant height, especially when grown in medium enriched with banana pulp. During the ex vitro phase, plants originating from bioreactors continued to show the highest results, especially those cultivated in medium with the addition of banana. This study is the first to investigate the use of temporary immersion bioreactors in the micropropagation of C. nobilior, demonstrating that the combination of bioreactor and culture media supplemented with banana pulp provides optimal conditions for the robust growth of plants, both in vitro and ex vitro, offering new perspectives for the commercial production and conservation of the species.